Baseline and multinormal distribution of ex vivo susceptibilities of Plasmodium falciparum to methylene blue in Africa, 2013–18. (14th May 2020) - Gendrot, Mathieu; Madamet, Marylin; Mosnier, Joel; Fonta, Isabelle; Amalvict, Rémy; Benoit, Nicolas; Briolant, Sébastien; Pradines, Bruno
Abstract: Background: Plasmodium falciparum resistance to most antimalarial compounds has emerged in Southeast Asia and spread to Africa. In this context, the development of new antimalarial drugs is urgent. Objectives: To determine the baseline in vitro activity of methylene blue (Proveblue ® ) on African isolates and to determine whether parasites have different phenotypes of susceptibility to methylene blue. Methods: Ex vivo susceptibility to methylene blue was measured for 609 P. falciparum isolates of patients hospitalized in France for malaria imported from Africa. A Bayesian statistical analysis was designed to describe the distribution of median effective concentration (EC50 ) estimates. Results: The EC50 ranged from 0.16 to 87.2 nM with a geometric mean of 7.17 nM (95% CI = 6.21–8.13). The 609 EC50 values were categorized into four components: A (mean = 2.5 nM; 95% CI = 2.28–2.72), B (mean = 7.44 nM; 95% CI = 7.07–7.81), C (mean = 16.29 nM; 95% CI = 15.40–17.18) and D (mean = 38.49 nM; 95% CI = 34.14–42.84). The threshold value for in vitro reduced susceptibility to methylene blue was estimated at 35 nM using the geometric mean of EC50 plus 2 SDs of the 609 isolates. This cut-off also corresponds to the lower limit of the 95% CI of the methylene blue EC50 of component D. Thirty-five isolates (5.7%) displayed EC50 values above this threshold. Conclusions: Methylene blue exerts a promising efficacy against P. falciparum and is a potential partner for triple combinations.